Moral Injury: An Integrative Review - Griffin, Brandon J.; Purcell, Natalie; Burkman, Kristine; Litz, Brett T.; Bryan, Craig J.; Schmitz, Martha; Villierme, Claudia; Walsh, Jessica; Maguen, Shira (Journal of traumatic stress, 2019)
Individuals who are exposed to traumatic events that violate their moral values may experience severe distress and functional impairments known as “moral injuries.” Over the last decade, moral injury has captured the attention of mental health care providers, spiritual and faith communities, media outlets, and the general public. Research about moral injury, especially among military personnel and veterans, has also proliferated. For this article, we reviewed scientific research about moral injury. We identified 116 relevant epidemiological and clinical studies. Epidemiological studies described a wide range of biological, psychological/behavioral, social, and religious/spiritual sequelae associated with exposure to potentially morally injurious events. Although a dearth of empirical clinical literature exists, some authors debated how moral injury might and might not respond to evidence‐based treatments for posttraumatic stress disorder (PTSD) whereas others identified new treatment models to directly address moral repair. Limitations of the literature included variable definitions of potentially morally injurious events, the absence of a consensus definition and gold‐standard measure of moral injury as an outcome, scant study of moral injury outside of military‐related contexts, and clinical investigations limited by small sample sizes and unclear mechanisms of therapeutic effect. We conclude our review by summarizing lessons from the literature and offering recommendations for future research. Resumen Spanish s by Asociación Chilena de Estrés Traumático (ACET) Daño Moral: Una revisión integrativa REVISION INTEGRATIVA DE LA INVESTIGACION EN DAÑO MORAL Las personas que están expuestas a eventos traumáticos que violan sus valores morales pueden experimentar una angustia grave y discapacidades funcionales conocidas como “daño moral”. En la última década, el daño moral ha captado la atención de proveedores de servicios de salud mental, comunidades espirituales y religiosas, medios de comunicación y el público en general. La investigación sobre daño moral, especialmente entre el personal militar y los veteranos, también ha proliferado. Para este artículo, revisamos la investigación científica sobre el daño moral. Se identificaron 116 estudios epidemiológicos y clínicos relevantes. Los estudios epidemiológicos describieron una amplia gama de secuelas biológicas, psicológicas / conductuales, sociales y religiosas / espirituales asociadas con la exposición a eventos potencialmente dañinos moralmente. Aunque existe una escasez de literatura clínica empírica, algunos autores debatieron cómo el daño moral podría y no podría responder a los tratamientos basados ​​en la evidencia para el trastorno de estrés postraumático (TEPT), mientras que otros identificaron nuevos modelos de tratamiento para abordar directamente la reparación moral. Las limitaciones de la literatura incluyeron definiciones de variables de eventos potencialmente perjudiciales desde el punto de vista moral, la ausencia de una definición consensuada y una medida de gold‐estándar de daño moral y sus consecuencias, escaso estudio de daño moral fuera de contextos relacionados con el ejército e investigaciones clínicas limitadas por muestra de tamaño pequeños y mecanismos poco claros del efecto terapéutico. Concluimos nuestra revisión resumiendo las lecciones de la literatura y ofreciendo recomendaciones para futuras investigaciones. 抽象 Traditional and Simplified Chinese s by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Moral Injury: An Integrative Review Traditional Chinese 標題: 道德創傷:一項綜合評估 撮要: 經歷與自己的道德價值相違的創傷事件, 可導致嚴重悲痛和功能損傷, 此為「道德創傷」。過去十年來, 心理治療人士、信仰團體、媒體和普羅大眾開始關注道德創傷, 而針對道德創傷的研究, 特別是專門檢視現役和退役軍人的研究, 亦大大提升。本文將審視有關道德創傷的科學研究, 找出116份相關的流行病學及臨床研究。流行病學研究描述跟經歷潛在會導致道德創傷的事件相關的生物學、心理/行為、社會、信仰/精神層面廣泛的後遺症。雖然目前只有少量具臨床實證的文獻, 但當中有些探討針對創傷後壓力症(PTSD)的實證為本治療是否能治理道德創傷, 有些則找出新的治療模型以直接治理道德創傷。這些文獻的限制, 包括對潛在會導致道德創傷的事件有不同定義、缺乏對定義的共識、未能得出測量道德創傷的黃金標準、缺乏軍事相關環境以外的道德創傷研究, 而臨床研究的樣本數量小而且療效的機制模糊。最後, 我們總結文獻帶來的貢獻, 並為未來研究提供建議。 Simplified Chinese 标题: 道德创伤:一项综合评估 撮要: 经历与自己的道德价值相违的创伤事件, 可导致严重悲痛和功能损伤, 此为「道德创伤」。过去十年来, 心理治疗人士、信仰团体、媒体和普罗大众开始关注道德创伤, 而针对道德创伤的研究, 特别是专门检视现役和退役军人的研究, 亦大大提升。本文将审视有关道德创伤的科学研究, 找出116份相关的流行病学及临床研究。流行病学研究描述跟经历潜在会导致道德创伤的事件相关的生物学、心理/行为、社会、信仰/精神层面广泛的后遗症。虽然目前只有少量具临床实证的文献, 但当中有些探讨针对创伤后压力症(PTSD)的实证为本治疗是否能治理道德创伤, 有些则找出新的治疗模型以直接治理道德创伤。这些文献的限制, 包括对潜在会导致道德创伤的事件有不同定义、缺乏对定义的共识、未能得出测量道德创伤的黄金标准、缺乏军事相关环境以外的道德创伤研究, 而临床研究的样本数量小而且疗效的机制模糊。最后, 我们总结文献带来的贡献, 并为未来研究提供建议。